Análise de riscos de mercado no apreçamento das indústrias do setor de alimentos - estudo de casos - Godoy, Julianne (2012)
The objective of this paper is to verify whether all predictive information regarding the market risks mentioned on prospect of listed companies, required by CVM – Comissão de Valores Mobiliários (Securities and Exchange Commission of Brazil), helping to explain the profitability of companies. Four (4) analysis will be performed for companies in the food sector (case study) using 2 (two) models: 1) The traditional CAPM – Capital Asset Pricing Model; 2) APT – Arbitrage Pricing Theory, including as variables the return over the IBOVESPA market portfolio and the variables informed on the financial reports and documents of the companies in compliance with CVM. Applying and comparing these models will also enable us to infer the best pricing model for such companies, based on the results found.